1995
DOI: 10.2307/3053918
|View full text |Cite
|
Sign up to set email alerts
|

Language, Law, and Society: Policy Implications of the Kennedy Smith Rape Trial

Abstract: In this article I examine the applied relevance of trial talk for rape shield legislation and attempts to evaluate the impact of such legal reforms. Using linguistic data from the Kennedy Smith rape trial, I argue that attempts to progressively implement rape shield have thus far failed and that research evaluating its impact has been more or less misguided because reformers and researchers have consistently failed to scrutinize empirically the interactional object to which rape shield legislation is applied: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…The law is a language of symbolic power (Goodrich 1990;Bourdieu 1987) that, among other ways, manifests itself in legal labelling, legal categorisation, different negotiation discourses, and control over meaning, and as an instrument and expression of domination (Conley et al 1978;Goodrich 1990; see also Matoesian 1995;Newman 2013). Lawyers, judges, and legal aid workers, etc., should pay attention to their translation skills.…”
Section: Translating the Law Into Everyday Languagementioning
confidence: 99%
“…The law is a language of symbolic power (Goodrich 1990;Bourdieu 1987) that, among other ways, manifests itself in legal labelling, legal categorisation, different negotiation discourses, and control over meaning, and as an instrument and expression of domination (Conley et al 1978;Goodrich 1990; see also Matoesian 1995;Newman 2013). Lawyers, judges, and legal aid workers, etc., should pay attention to their translation skills.…”
Section: Translating the Law Into Everyday Languagementioning
confidence: 99%
“…Despite rape shield laws, the following evidence remains admissible in criminal cases: evidence of specific instances of sexual behavior by the alleged victim offered to prove that a person other than the accused was the source of injury, semen or other physical evidence, evidence of specific instances of sexual behavior between the alleged victim and the accused offered to prove consent, or evidence that the exclusion of the victim's sexual history would violate the defendant's constitutional rights (Ibid.). The least restrictive rape shield law allows judges discretion to determine what information about the victim's sexual history will be admitted as evidence during the trial (Matoesian, 1995).…”
Section: Rape Shield Lawsmentioning
confidence: 99%
“…These laws attempt to limit the defense attorney's opportunities to subject the victim to irrelevant attacks on her character and credibility. By removing this trauma-generating factor during the trial, it was anticipated that victims would report rape more readily, that the state would be more willing to prosecute, and that juries would be more likely to convict suspected rapists (Matoesian 1995). However, although rape shield legislation may make a different ideological statement about gender relations, an analysis of the talk in rape trials reveals that men's power over women seems little changed (Matoesian 1993).…”
Section: The Revictimization Of Rape Victimsmentioning
confidence: 99%
“…By removing this trauma-generating factor during the trial, it was anticipated that victims would report rape more readily, that the state would be more willing to prosecute, and that juries would be more likely to convict suspected rapists (Matoesian 1995). However, although rape shield legislation may make a different ideological statement about gender relations, an analysis of the talk in rape trials reveals that men's power over women seems little changed (Matoesian 1993). In Matoesian's study of rape trials (1993) two domains of power are identified: courtroom disciplinary regimes that organize participation rights and access to talk, and patriarchal domination that is enacted through moral inferential practices.…”
Section: The Revictimization Of Rape Victimsmentioning
confidence: 99%
See 1 more Smart Citation